Clinical and prognostic value of the MELD-XI score in hospitalized patients with chronic heart failure - N. A. Dragomiretskaya; V. I. Podzolkov; A. V. Tolmacheva; I. I. Shvedov; M. V. Vetluzhskaya; V. D. Chistyakova (Рациональная фармакотерапия в кардиологии)
Aim: to evaluate the diagnostic and prognostic role of the MELD-XI index in hospitalized patients with CHF.Material and methods: The prospective study included 182 patients (92 men and 90 women), age 72.3±12.1 years, hospitalized at Clinical Hospital No. 4 of the First Moscow State Medical University with the CHF class II-IV. All patients signed the informed consent and underwent a standard examination with determination of NTproBNP and calculation of the MELD-XI index = 5.11 (ln [total bilirubin, mg/dl]) + 11.76 (ln [creatinine, mg/dl]) + 9.44. The primary endpoint was death from all causes within 36±3 months.Results: Based on the median MELD-XI index, 2 groups of patients were identified - high MELD-XI index>11.4 points (n=85 (47%)) and low - MELD-XI<11.4 points (n=97 (53 %)). Patients in the groups were comparable in age, comorbid diseases, and main classes of drug therapy received. Patients with a high MELD-XI index were characterized by a more severe course of stage IIB-III CHF and low LVEF (42.5[37; 50]% vs 52 [40; 60], p=0.0005).All-causes death over 3 years of follow-up was 39.6%. In patients who reached the end point, regardless of their initial LVEF, MELD-XI index values ​​were significantly higher (12.2 [9.7; 15.2] points) compared to survivors (10,6 [8,2;12,8] points (p<0.001)). According to ROC analysis, the threshold value of the MELD-XI index for high risk of death was 11.4 points (sensitivity 62.73%, specificity 59.15% (AUC 0.634; p=0.03)). Regression analysis showed that MELD-XI index values ​​>11.4 points increase the risk of death by 2.3 times (OR: 2.345, 95% CI: 1.274-4.315, p = 0.006) and are independent significant predictors of poor prognosis, along with LVEF <40%, NT-proBNP and sST2 levels and community-acquired pneumonia. Each subsequent 1-point increase in MELD-XI score increases the odds of death by 1.157 times (OR: 1.157, 95% CI: 1.0616-1.261, p<0.01)Conclusion: The MELD-XI score is a simple and reliable method for diagnosing multiple organ dysfunction in patients with CHF. MELD-XI index>11.4 points is a predictor of poor long-term prognosis in hospitalized patients with CHF.